Cultural Terms in Translation: A Study Of Colleen Hoover’s It Ends with us Novel and Its Translation - Denia Agyta Larasati; Nurochman, Nurochman (International Journal of English and Applied Linguistics (IJEAL), 2024)
This study investigates the cultural terms used in the It Ends With Us novel by Colleen Hoover, aiming to identify various cultural terms and analyze their function within the novel. Employing a qualitative approach, the research draws data directly from the novel. The researcher applies Newmark’s framework to identify different cultural terms and utilizes Chesterman’s theory to analyze the strategy of translations applied in the novel. The research findings indicate the presence of 46 data on cultural terms, which were translated using seven techniques outlined by Chesterman (2016). These techniques include literal translation, which are 3 data, 1 data involved using a loan strategy, 1 data involved using an information strategy, 11 data involved using an expansion strategy, 11 data involved using a compression strategy, 14 data involved using unit shift, and 2 data involved using a calque, 1 data involved using transposition, 1 data involved using synonymy strategy, and 1 data of hyponymy. The strategy used in the novel is a unit shift strategy. This decision ensured the accurate acceptance of the information conveyed by the novel's original author among the target readers. The research found the types applied in the translated text into 5, which are 1 data on ecology, 20 data on material, 1 data on social culture, 6 data on political and social organization, and 12 data on gesture and habit.